2021
DOI: 10.4995/jarte.2021.14741
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of waiting time of patients by queuing techniques: case study of large hospital in Pakistan

Abstract: <p class="JARTEAbstractHeader">The purpose of this empirical research was to analyze the comfortable waiting time (CWT) of patients at the outpatient department (OPD) of Gastrology of ABC hospital of Karachi. It is based on the analysis of CWT of patients who were being served at the OPD of Gastrology of ABC hospital of Karachi. The data was collected by the help of questionnaire. Altogether 250 questionnaires were distributed among the patients, 210 of them were collected back and 10 of them were incomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Still, the percent of land use might boost up to 30.7% when the most affordable and also the highest diversification scenarios were contrasted (Woubante, 2017). The queue is prevalent in day to day life (Kalwar et al, 2018;Kalwar, Mari, et al, 2020;Kalwar, Memon, et al, 2021;Khan, Khaskheli, et al, 2021b, 2021aKhaskheli et al, 2020). Solaja et al, (2019) conducted their research in feed production mills; he suggested that choice makers ought to not base their decision on experience and intuition, yet on the analytical and also technical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the percent of land use might boost up to 30.7% when the most affordable and also the highest diversification scenarios were contrasted (Woubante, 2017). The queue is prevalent in day to day life (Kalwar et al, 2018;Kalwar, Mari, et al, 2020;Kalwar, Memon, et al, 2021;Khan, Khaskheli, et al, 2021b, 2021aKhaskheli et al, 2020). Solaja et al, (2019) conducted their research in feed production mills; he suggested that choice makers ought to not base their decision on experience and intuition, yet on the analytical and also technical approach.…”
Section: Discussionmentioning
confidence: 99%
“…In operations research, different techniques are used for simplification of industrial issues i.e. management of the queuing system by use of queuing theory (Kalwar, Khaskheli, Khan, Siddiqui, & Gopang, 2018;Kalwar, Mari, Memon, Tanwari, & Siddiqui, 2020;Kalwar, Marri, Khan, & Khaskheli, 2021;Kalwar, Memon, Khan, & Tanwari, 2021;Khan, Khaskheli, et al, 2021a, 2021bKhaskheli, Marri, Nebhwani, Khan, & Ahmed, 2020), efficient allocation of resources by use of linear programming (Addy, 2014;Akpan & Iwok, 2016;Alvfors & Björelind, 2015;Aregawi, 2018;Gameiro, Rocco, & Caixeta Filho, 2016;Jain, Bhardwaj, Saxena, & Choubey, 2019;Jyothi, Rao, & Sivasundari, 2019;Maurya, Misra, Anderson, & Shukla, 2015;Tesfaye, Berhane, Zenebe, & Asmelash, 2016;Workie, Alemu A, & Asmelash, 2016;Woubante, 2017;Yoanita, 2016;Yu, 2015;Yue, 2013), and so on. Optimization and Operational research methods are thoroughly used to acquire better options and decisions to industrial issues (Jyothi et al, 2019;Nawrocki, 2013).The industrial development strategy is identified by the reliable use of resources at every production stage.…”
Section: Introductionmentioning
confidence: 99%
“…Because of manual reporting in Microsoft Excel, a lot of time was used to be spent on the formation of reports, and the purchasing department used to wait because of many order costing reports in the queue. Since, waiting cost is associated with queues (Kalwar et al, 2018;Kalwar, Mari, et al, 2020;Kalwar, Memon, et al, 2021;Khan, Khaskheli, et al, 2021a, 2021bKhaskheli et al, 2020), thus it was decided to automate the order costing report. The procedure to make an order costing report was manual e.g.…”
Section: Suggested Methods For Preparation Of Order Costing Reportmentioning
confidence: 99%